-x+9=-5x+39

Simple and best practice solution for -x+9=-5x+39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+9=-5x+39 equation:



-x+9=-5x+39
We move all terms to the left:
-x+9-(-5x+39)=0
We add all the numbers together, and all the variables
-1x-(-5x+39)+9=0
We get rid of parentheses
-1x+5x-39+9=0
We add all the numbers together, and all the variables
4x-30=0
We move all terms containing x to the left, all other terms to the right
4x=30
x=30/4
x=7+1/2

See similar equations:

| 5x-2+9x=3x+3-5x | | y^2+22y+57=0 | | X+4(3x+32)=12 | | 64.60+4.25*31=10x | | -6(v+4)+2v+5=7v+10 | | 4(-2x+10)=-8x+40 | | 6(2x-6)=7(-2x+4) | | 7+0.10=0.15x+8 | | 40-3x=10 | | 5g+7-2g+1=12 | | -6x-44=2x+28 | | -12b+36=6(6-2b) | | h^2+5h-150=0 | | 16/x=60/40 | | 12.37=2g+3.59 | | 2(-3)-7y=17 | | (x+4)^2-4=16 | | -4(3x-6)=3(-4x+6) | | x/2-2=-9 | | 3x+4=80 | | h2+5h-150=0 | | 4y(y-4)=-20 | | 10=14-7(2x-4) | | 4x-16=2x-16+2x | | -1/2x-5=0 | | M+7(5m-3)=35+8m | | 12x+15+6x=24 | | 0.08t+3+2.50=13.80 | | (x-4)^2+4=36 | | 5(1-x)=5+5x | | 4(2x+6)=5x+25+2 | | -2(1+6w)+8(w+8)=79 |

Equations solver categories